Sustaining the Local Economy Through Islamic Production Management: A Case Study of The Kopi Mojago Home Industry in North Sulawesi - Mamonto, Teguh Setiawan; Jan, Radlyah Hasan; Haris, Chadijah; Korompis, Claudia Wanda Melati (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2025)
This study aims to analyze in depth the implementation of production management based on Islamic values in the Mojago Coffee home industry located in Bilalang 1 Village, Kotamobagu City, North Sulawesi. This study is crucial to fill the gap in the academic literature on how Sharia principles are practically internalized in micro business operations to support sustainable local economic resilience. This study uses a descriptive qualitative method with a field research approach. Empirical data collection was carried out through triangulation techniques, which included participant observations on the production flow, in-depth interviews with business owners and workers, and documentation studies. The results of the study show that Kopi Mojago applies unique operational management practices that are driven by religious consciousness (God-consciousness) and not just material profits. First, in the Planning function, the main priority is placed on the concept of Halalan Thayyiban through the strict selection of raw materials as well as seasonal inventory management strategies to mitigate the risk of uncertainty (gharar) and avoid waste (israf). Second, in Organization, a harmonious work structure based on Ukhuwah (brotherhood) is applied, where the wage system strictly adheres to the principle of Justice ('Adl) according to the workload and punctuality of payment. Third, the Direction function applies a prophetic leadership style that frames work activities as a manifestation of worship (jihad iqtishadi) and an example of leadership. Fourth, Supervision rests on the concept of Muraqabah (feeling supervised by Allah) as an internal self-control mechanism that is effective in preventing fraud (tadlis) and ensuring product quality. In addition, halal certification is a strategic instrument to build market trust. This study recommends that local governments provide technological assistance for the standardization of roasting machines and subsidize halal certification costs to empower the local creative economy.